2011
DOI: 10.1371/journal.pone.0024133
|View full text |Cite
|
Sign up to set email alerts
|

Despotism and Risk of Infanticide Influence Grizzly Bear Den-Site Selection

Abstract: Given documented social dominance and intraspecific predation in bear populations, the ideal despotic distribution model and sex hypothesis of sexual segregation predict adult female grizzly bears (Ursus arctos) will avoid areas occupied by adult males to reduce risk of infanticide. Under ideal despotic distribution, juveniles should similarly avoid adult males to reduce predation risk. Den-site selection and use is an important component of grizzly bear ecology and may be influenced by multiple factors, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 62 publications
3
43
0
Order By: Relevance
“…Relative influence of standardized covariates for the combined (second step) top models representing patterns of selection of denning sites by brown bears (Ursus arctos) at the home range scale (third order) across the central Brooks Range, Alaska, USA, 2014-2017. The average (31°) and the range (16°-44°) of slopes of dens were similar to other studies (Reynolds et al 1974, Libal et al 2011, 2012 and may represent the range of slopes providing stable and thermally optimal conditions for excavating dens (Reynolds et al 1974, Vroom et al 1980b, Libal et al 2012. Dots represent estimated coefficients, error bars depict the 95% confidence intervals, SLI indicates snow load index, DTD indicates distance to den in previous year, and Salmon indicates distance to salmon stream.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Relative influence of standardized covariates for the combined (second step) top models representing patterns of selection of denning sites by brown bears (Ursus arctos) at the home range scale (third order) across the central Brooks Range, Alaska, USA, 2014-2017. The average (31°) and the range (16°-44°) of slopes of dens were similar to other studies (Reynolds et al 1974, Libal et al 2011, 2012 and may represent the range of slopes providing stable and thermally optimal conditions for excavating dens (Reynolds et al 1974, Vroom et al 1980b, Libal et al 2012. Dots represent estimated coefficients, error bars depict the 95% confidence intervals, SLI indicates snow load index, DTD indicates distance to den in previous year, and Salmon indicates distance to salmon stream.…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, other studies have shown a relationship between densite selection and forage availability for brown bears (Libal et al 2011, Pigeon et al 2014. We posit that the energetic output for bears to travel between areas with important food resources and den sites is relatively low compared to the energy saved by selecting den features that reduce disturbances and improve thermal insulation over a 6-to 8month hibernation period.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…; Libal et al . ). Spatiotemporal avoidance of infanticidal individuals is an obvious counterstrategy, but conclusive evidence for it is rare and mainly involves group‐living species (Ebensperger & Blumstein ) such as lions ( Panthera leo ) (Pusey & Packer ) and Hanuman langurs ( Presbytis entellus ) (Hrdy ).…”
Section: Introductionmentioning
confidence: 97%
“…; Bellemain, Swenson & Taberlet ; Libal et al . ). Female counterstrategies to NPI in brown bears include direct defence (Craighead, Sumner & Mitchell ), promiscuity and multiple paternity (Bellemain, Swenson & Taberlet ), selecting escape habitat (Pearson ; Swenson ), elusiveness (Dahle & Swenson ) and avoidance of sites with high infanticide risk (e.g.…”
Section: Introductionmentioning
confidence: 97%